Evaluation of surgical outcomes and causes of recurrence in thyroglossal duct cyst referring a referral children hospital in Iran from 2011 to 2018 - Leili Mohajerzadeh; Sadaf Yazdani; Mehdi Sarafi; Ahmad Eghbali; AmirMohammad Zakeri (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Thyroglossal duct cyst is amongst the most common congenital anomalies in the neck region which is only properly treated with surgery. However, the long-term result remains uncertain. The present study aimed to assess surgical outcomes and predictors of recurrence in cases of thyroglossal duct cyst that have been referred to a tertiary level children hospital in Iran. Materials and Methods:  In this cross-sectional study, 29 children with thyroglossal duct cyst that had undergone Sistrunk procedure in Mofid hospital between 2011 and 2018 were evaluated. The study information was collected by reviewing the hospital charts. Results: Patient's age ranged between 20 and 40 months. The disease in boys was twice as prevalent as girls and hence male to female ratio was almost equal to 2 to 1. Palpable cervical mass was the most prevalent which we found in 62.1%, followed by painful neck mass (13.8%), discharging cutaneous fistula (13.8%), palpable mass with dysphagia (6.9%) and abscess (3.4%). Preoperative antibiotics were prescribed for infection in 34.5%. Regarding the position of the thyroglossal duct cyst, suprahyoid position was reported in 72.4%. In terms of type of surgery, 23 cases (79.3%) underwent sistrunk procedure and 6 cases (20.7%) underwent simple incision. The mean follow-up time for patients was 3.32 ± 1.42 years. The relapse rate after surgery was 6.9% and the rate of postoperative complications was 10.3%. The percentage of relapse-free survival was 91.3% during the follow up period. The presence of discharging fistula as the predominant manifestation (p = 0.009), preoperative infection (p = 0.043), and thyrohyoid position (p = 0.016) were related to the disease recurrence. Conclusion: Surgical complications rate including relapse or infections was 10.3% and the incidence of recurrence after surgery during the follow-up period with a mean of three years was 6.9%; that is more prevalent in patients with the presence of discharging fistula, preoperative infection, or thyrohyoid position. Preoperative infections, rather than postoperative infections, are associated with more recurrence. Thus infection is very important factor in the recurrence of thyroglossal duct cyst.